Kebijakan Hukum Pidana Sebagai Regulasi Dalam Penanggulangan Cyber Crime Di Indonesia - Maya Sri Novita (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
The globalization of information technology has brought the world into the era of cyberspace, where Internet facilities present the virtual world with its virtual reality and offer various hopes and opportunities to society. However, there is a problem in the form of a crime called cybercrime. This crime does not recognize national borders (no Borders) or time, because often the victims and perpetrators are in different countries. Cybercrime can be committed through the same computer network system as the target and the computer itself as a means to commit a crime. The rapid development of information technology must be taken into account with the laws and regulations governing it. The negative impact must be anticipated and overcome through legal regulation of the use of information and communication technology. Based on these problems, research was conducted on criminal policies to eradicate cybercrime in Indonesia. The purpose of this research was to understand the criminal law policy based on the Criminal Code to eradicate cybercrime in Indonesia and to study the criminal law policy based on the ITE Law to eradicate cybercrime in Indonesia. The central approach in this research was normative law, because the discussion was based on legal regulations and legal principles that apply to the topic of cybercrime. The legal approach aimed to conduct research in the field of law, especially criminal law. Law enforcement efforts are not only limited to capacity building, law enforcement facilities and infrastructure, but also accompanied by public awareness of the law supported by cooperation with Internet service providers